Eksplorasi Diplomasi Budaya Indonesia Dalam Perhelatan Bali Street Carnival - Mahhendra, M. Riza; Putra, Dhani Afan Rahman; Luerdi, Luerdi (PT. Faaslib Serambi Media, 2025)
This research aimed to explore Indonesia’s cultural diplomacy through the Bali Street Carnival, a side event of the 10th World Water Forum. The carnival was a cultural parade showcasing various arts and local traditions, and it became a medium of diplomacy to introduce Balinese culture and Indonesia in general. Through the qualitative method with a case study, this research investigated how such events contributed to cultural diplomacy, strengthened international relationships, and promoted sustainability. The findings demonstrate that the cultural carnival became a platform to introduce Indonesia’s culture, bridge intercultural understanding, promote marine conservation, and encourage global awareness of environmental issues.